Analysis of physical aspects in the interior of static spherical spacetime admitting Durgapal-IV spacetime in f(Q,T) theory - M. Zeeshan Gul; M. Sharif; Adeeba Arooj; Faisal Javed (Nuclear Physics B, 2025)
Our paper examines effect of the recently developed f(Q,T) theory on a structure of dense objects containing dense matter distribution. For this purpose, we consider viable solutions to study the interior region of considered compact stars. With the Darmois constraints we evaluate unidentified constants of metric coefficients. Additionally, assume a precise f(Q,T) theory model to reduce complication of the system and obtain explicit equation of matter contents that further used to investigate various physical parameters in the interior of considered compact objects. The equilibrium state for dense compact stars is determined by the TOV equations. The stability state for the compact stars is determined by the causality method. We finalize that the anisotropic spheres in f(Q,T) theory background are feasibly stable.